Self Stretching Exercise Lebih Efektif Dibandingkan Mckenzie Exercise Dalam Mengurangi Keluhan Low Back Pain Non-Spesifik - Mandowen, Gracia Silvany Yustina; Suparwati, Komang Tri Adi; Jaya, I Putu Prisa; Manuaba, I.A. Ratih Wulansari (Jurnal Kedokteran Meditek, 2025)
Introduction: The activities of garment workers who work with repetitive movements over a long time can influence the emergence of musculoskeletal complaints, one of which is low back pain, which is non-specific. Low back pain non-specific complaints impact functional activities and affect workers' work. Purpose: This study aims to determine the effect of the stretching exercise and McKenzie exercise in reducing pain and increasing functional activity in garment workers with non-specific low back pain. Methods: This type of research is experimental with a pre-test and post-test control group design. Treatment is given in 12 sessions over 4 weeks and carried out from April to May 2024. The research subjects were garment workers who met the inclusion and exclusion criteria with 22 people, divided into group I (n = 11 people) given the stretching exercise and group II (n = 11 people) given the McKenzie exercise. Results: The results of the difference test between groups I and II used the Mann-Whitney U test on the Visual Analog Scale (p < 0.05) and Oswestry Disability Index values (p < 0.05). Methods: It was concluded that self-stretching exercise was more effective than McKenzie exercise in reducing pain and increasing functional activity in garment workers with non-specific lower back pain